To Serve and Protect? An Empirical Study of Police-Involved Sexual Assault - McNabb, Danielle (Women & criminal justice, 2024)
Sexual assault is among the most challenging offenses to investigate and prosecute, a reality that is exacerbated when the perpetrator is a police officer. In this article, we analyze the attrition of 689 reports of police-involved sexual assault made to the Ontario Special Investigations Unit, between 2005 and 2020. The findings reveal that the vast majority of sexual assault reports do not result in criminal charges, with only 1.59% of complaints resulting in a conviction and sentence. We situate these findings within the wider context of criminal justice responses to sexual violence and police oversight and make suggestions for reform.